EFL Students’ Perceptions on Using Grammarly in Thesis Writing at English Education Department Students - Driane, Luthfi Azhaar; Roza, Veni; Melani, Melyann; Reflinda, Reflinda (Pusdikra Publishing, 2024)
This research aimed to identify EFL students’ perceptions of using Grammarly in writing their theses. Several problems were found in this research. Firstly, some EFL students utilized Grammarly for their thesis writing. Secondly, some EFL students did not understand how to use Grammarly. This research was descriptive qualitative research. The informants of this research were 7 students from English Education Department Class of 2023 who used Grammarly Premium in thesis writing. To gather data, this research used semi-structured interviews as the primary instrument. This research categorized the interview questions into three key indicators: interest, needs, and experience. The data were analyzed using an interactive model analysis, and each informant was interviewed individually. The findings revealed that students perceived positively when using Grammarly in writing their thesis. The interview data demonstrated that students expressed positive views in terms of interest, needs, and experience. EFL students considered Grammarly trusted resource in thesis writing. Their positive experiences highlighted the application’ effectiveness in enhancing overall writing quality for student.